Cognitive and Neurocognitive Effects From the Unique Bilingual Experiences of Interpreters - Ferreira, Aline; Schwieter, John W.; Festman, Julia (Frontiers in Psychology, 2020)
For bilinguals, research suggests that both languages are constantly active and competing in the mind, even when only using one. However, this body of work has reported inconclusive results on the long-term effects of the constant parallel activation and use of more than one language on the brain. This has mostly been due to inconsistent comparisons between groups of bilinguals and monolinguals. Not all bilingualisms are the same. The investigation of the use of more than one language over a lifetime offers the opportunity to better understand the consequences of bilingualism on the brain. However, few studies have specifically looked at the long-standing effects of being an interpreter. In this paper, we review theories from the field of Translation and Interpreting Studies and provide a critical review of work that offers insight on the cognitive and neurocognitive effects that seem to arise from the unique, highly-cognitive-demanding practices experienced by interpreters.